2020
DOI: 10.1021/acs.jafc.0c05800
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Alleviates Atherosclerosis in ApoE–/– Mice by Regulating Cholesterol Metabolism Involved in Gut Microbiota Remodeling

Abstract: Naringin, a major flavonoid in citrus, has potential for preventing atherosclerosis. The presence in the colon of a large amount of naringin after oral intake might affect the gut microbiota. We investigated the role of gut microbiota remodeling in the alleviation of atherosclerosis by naringin. Naringin significantly alleviated atherosclerosis and lowered the serum and liver cholesterol levels by 24.04 and 28.37% in ApoE −/− mice fed with a high-fat diet. Nontarget metabolomics showed that naringin modulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…Our previous study revealed eight new ene-yne hydroquinones derived from marine fungus Pestalotiopsis neglecta SCSIO41403, one of them, pestalotioquinoside C (102), functioning as a potential LXRα agonist via upregulating the mRNA level of the target gene ABCA1. Using SPR assay, 102 interacted with LXRα dose-dependently with the K D of 50.0 μM ( Wang F. et al, 2020 ). Further study discovered pestalotiochromones A (103) as a potential LXRs agonist, remarkably upregulated LXRβ and downstream gene ABCA1.…”
Section: Natural Products Targeting Liver X Receptorsmentioning
confidence: 99%
“…Our previous study revealed eight new ene-yne hydroquinones derived from marine fungus Pestalotiopsis neglecta SCSIO41403, one of them, pestalotioquinoside C (102), functioning as a potential LXRα agonist via upregulating the mRNA level of the target gene ABCA1. Using SPR assay, 102 interacted with LXRα dose-dependently with the K D of 50.0 μM ( Wang F. et al, 2020 ). Further study discovered pestalotiochromones A (103) as a potential LXRs agonist, remarkably upregulated LXRβ and downstream gene ABCA1.…”
Section: Natural Products Targeting Liver X Receptorsmentioning
confidence: 99%
“…The final 3 articles selected are from Korea (2001) 8 , China (2020) 9 , and France (2012) 10 . A total of 92 animal models used in these studies were hypercholesterolemia.…”
Section: Resultsmentioning
confidence: 99%
“…PNS regulates the balance of intestinal flora and is an important starting point for repairing the mucosal barrier. Its main ingredients include paeoniflorin, naringin, hesperidin, and neohesperidin which also play an important role in the regulation of intestinal flora [42][43][44][45]. is study confirmed that compared with the DSS group, the diversity of intestinal flora increased after PNS administration (Figure 3(a)), and the abundance Evidence-Based Complementary and Alternative Medicine of Bacteroides, Staphylococcus, Odoribacter, Lactobacillus, Isobacterium, and other bacteria increased, while Escherichia-Shigella bacteria, Helicobacter, Streptococcus, and other bacteria were significantly reduced (Figure 3(c)).…”
Section: Discussionmentioning
confidence: 99%